A Guide to Incorporating UpToDate into Curriculum - Kabale University Library (Kabale University, 2023)
The Better Evidence for Training program based at Ariadne Labs—a joint center for health systems innovation at Brigham and Women’s Hospital and Harvard T.H. Chan School of Public Health—aims to enhance access to and uptake of the latest clinical evidence among future health care providers, encourage the habit of consulting evidence-based clinical resources, and ultimately, to support better patient care everywhere, for everyone, every time. UpToDate is an evidence-based digital tool used by 1.9 million clinicians in over 190 countries, including 90% of major academic medical centers in the United States. The tool aids in clinical decision making and has been shown to improve patient outcomes. Better Evidence research found that introducing UpToDate to medical students in Rwanda helped them habituate to consulting the evidence as part of clinical decision making after graduation. Benefits of introducing the tool to medical students and residents early in their career include: ● Demonstrating the importance of evidence-based care ● Habituating students to consult digital tools in practice ● Ensuring they have access to the latest clinical information to prepare for exams and provide care for patients UpToDate can also be used by clinical faculty and staff to improve their teaching. This document outlines some of the many ways UpToDate can be integrated into curriculum as part of the process of rolling out Better Evidence at your institution.